Anáfora indireta : uma dimensão cognitiva da linguagem em textos publicitários - Vargas, Maria Elizabete Borges (2009)
In this paper, we will analyze some publicity slogans advertised on Veja Magazine, and on the internet, between the years of 2004 and 2007. We start from the assumption that this textual style presents the interaction between product and consumers as main focus, making use of linguistic and perceptive-cognitive resources. We understand language as a combined action and as a phenomenon, at the same time, social and cognitive. To guide our thoughts, we shortly visited the considerations that Vygotsky and Van Dijk establish between language, cognition and the reading comprehension while cognitive process. In this perspective, we managed to analyze a textual style that reaches the more diversified audiences: the publicity text which is, undoubtedly, one of the styles with more chances to instigate desire and promote social welfare. When circumscribing the social practices in consumption promotion, we contemplated how publicity outlines its linguistic-cognitive constructions facing the Referencing Studies more precisely about the occurrence of indirect anaphors to better understand the employment of the indefinite pronoun (everything). We consider that there is, in this very lacunar indefinite pronoun , an explicit occurrence of indirect anaphora, which main role is, not only encapsulate, but to anchorage from a cognitive process. This anchor is placed in contextual elements implicit focuses stored in our memory from organized world knowledge and not only (co)textual so it s given a discursive inference. Hence, we found this approach in studies about Referencing, more specifically the indirect anaphora, undertheoretic orientation from Koch and Marcuschi. We intend to demonstrate that the Indirect Anaphora demands a higher cognitive cost than normally occurs with the anaphors, besides, consequently, readers would use different world knowledge to understand them. Generally, anaphoric expressions are previewed on the semantic theories as referent introductory. What we will try to demonstrate is that the Indirect Anaphora not always assumes a (co)textual antecedent, but, however, a cognitive antecedent, that varies, depending on the point of view and world knowledge, from reader to reader, as well as of the intention and cognitive anchor, from publicity to publicity. In this matter, we believe that this choice for the Indirect Anaphora influences the success of the advertising, as it cooperatively builds and subjects worlds with the reader/consumer, for this relying on linguistic resources